Intestinal Function after Early versus Late Appendectomy in Children with Perforated Appendicitis. Issue 1 (January 2019) - Munoz, Amanda; Hazboun, Rajaie; Vannix, Ian; Pepper, Victoria K.; Vannix, Rosemary; Tagge, Edward; Moores, Donald; Baerg, Joanne
The aim was to prospectively document the impact of early versus late appendectomy on intestinal function in pediatric perforated appendicitis. After Institutional Review Board approval, between September 2016 and August 2017, complete data were prospectively collected for children undergoing planned appendectomy for perforated appendicitis. One hundred children with pathologist-confirmed transmural perforations were included. The median time to operation after pain onset was three days. Operation on day 1 or 2 (early) was compared with that on day 3 or after (late) (range, 3–9 days). Emesis, nasogastric tubes, and time to tolerate diet evaluated intestinal function. Categorical and continuous variables were analyzed by chi-square and t tests. Of the 100, there were 45 in the early and 55 in the late group, with 22/55(40%) operated on day 3. Children with early appendectomy were significantly younger, 7.8 (3.5) versus 9.5 (3.8) years (P = 0.02). Pre-appendectomy, more than 80 per cent of each group had emesis (P = 0.84), but the late group had a 10-fold increase in nasogastric tube use (P = 0.02). The early group tolerated regular diet significantly faster, 2.5 (2.1) versus 4.4 (4.1) days (P = 0.01), and had a significantly shorter hospital stay, 3.5 (2.2) versus 5.6 (4.3) days (P = 0.01). When pain onset to appendectomy is less than three days, the time to return of intestinal function is significantly reduced.